PENGARUH WORK LIFE BALANCE DAN DUKUNGAN SOSIAL TERHADAP KINERJA GURU SMA NAHDATUL ULAMA 1 GRESIK - Adinda Amelia Firdaus; Maulidyah Amalina Rizqi (Universitas Sarjanawiyata Tamansiswa, 2026)
This study sought to assess how social support and work-life balance affected teachers' performance at SMA Nahdlatul Ulama 1 Gresik. Teachers in religious schools need to balance their social and professional life in order to succeed at their jobs. A survey was employed in conjunction with quantitative methodologies. 65 teachers from SMA Nahdlatul Ulama 1 Gresik participated in this study, and a saturation sampling technique was used to choose the sample. A validated questionnaire was used to gather data. The following data was processed using multiple linear regression analysis. The findings demonstrated that teacher performance was positively and significantly impacted by work-life balance. Furthermore, teacher performance at SMA Nahdlatul Ulama 1 Gresik was positively and significantly impacted by social support. According to this study, teachers might perform better when they have a healthy work-life balance and good social support